A Theoretical Investigation of Decorated Novel 1,2-Di(4-pyridyl)-ethylene based Dye Sensitized Solar Cells (DSSC) - KRISHNAVENI, S.; JOSEPHINE, X. MARY; MOHANKUMAR, S.; SATHYANARAYANAMOORTHI, V. (Asian Journal of Chemistry, 2023)
Density functional theory (DFT) approaches are employed to investigate the performance of dyes and the influence of p-conjugation in dye-sensitized solar cells (DSSCs). In this investigation, five new 1,2-di(4-pyridyl)-ethylene based conjugated donor-π-acceptor organic dyes (D-π-A) exist. The spacer is a diphenylamine (DPA) group, while the diphenyl amine group serves as the component that donates electrons in each system, the nitro/cyano group is used as an electron accepting group. An alternate methyl/ethyl group is employed as π-conjugated spacer in order to study the effect of the auxiliary donor group. Through performing DFT calculations with the B3LYP both the polarized split-valence 6-311++G (d,p) basis sets, an excitation energies, absorption spectra and emission spectra of each molecule were examined. The polarizable continuum model (PCM) is utilized in studying these impact for solvent. The energies at which these dyes are LUMO and HOMO, which assure the favourable impact for electron injection and these dye regeneration process. The calculation of the HOMO-LUMO gap demonstrates good agreement when compared to spectral information. The light-harvesting efficiency (LHE), electron injection free energy (ΔGinject), as well as oscillator strength (f) are computed and explained. The calculated open-circuit photovoltage values (Voc) and electron coupling constant (VRP) for the studied dye-sensitizers are also included in this study.